On the threshold of the amphibious voices: the acuatic imaginary in contemporary argentinian poetry (Anclajes, 2024)
The poetic works of Juan L. Ortiz, Francisco Madariaga, Martín Rodríguez and Javier Cófreces and Alberto Muñoz imagine an amphibian origin between childhood and language, between timeless myth and historical-political time, between the subjective and the impersonal, between nature and culture. Assuming a method of reading that is also amphibious (oscillating among the symbolic, phenomenological, psychoanalytic and political-aesthetic), we intend to explore the ways in which each of these works imagines, in a singular way, the space and time of origin as poetry, that is, making the word and the object coincide
Keywords: Juan L. Ortiz; Francisco Madariaga; Martín Rodríguez; Argentine poetry; XX Century